Education: the quest for the lost wisdom in the maze of knowledge - Al-Jaafar, Jubair; Al-Khateeb, Khalid A. Saeed; Lajis, Adidah (2007)
A novel method to assess the complex Education process has been devised. The technique involves the quantification of Learning Outcome, which has hitherto been largely subjective and cumbersome despite the technological advance in learning and teaching aids. The new technique presents an objective assessment in a mathematical form. The approach is an innovated Metric Suit based on a measure of Entropy related to learning outcome. The ‘Information’ entropy is computed and used as a measure of Knowledge. Another learning outcome is the proper application of relevant knowledge termed ‘Wisdom’. Wisdom can also be measured using entropy computations. In this sense, entropy is related to the factor of disorder. The various parameters are represented by random variables. Because the amount of the required computations is very large, only the most effective of variables will be considered. The results obtained so far are encouraging. However, more tests on the proposed Metric Suit from various areas of application will further ascertain its robustness. Comprehensive tests and thorough analyses will provide a strong basis for evaluation judgment. The model treats the education process as a communications channel. The transfer of information between the sender and the recipient depends on the amount of uncertainty presented by each of the components that constitute the system. The computations of “Entropy” involve all the programs that constitute a discipline at university level.